(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2020)
This study started from concern over the lack of respect between teachers and students, or vice versa. Based on these concerns, researchers sought to uncover the model of respect as applied in a school that based on humanistic values, namely SD Sanggar Anak Alam (SD Salam). Researchers conducted observations, interviews, and study documentation to obtain data on the implementation of a respectful attitude inside of learning and outside of learning. Then the data are analyzed using the stages of data display, data reduction, and conclusions. From this process, the researchers concluded that there were two forms of respect in SD Salam , There were (1) respect was realized through equal dialogue between students and facilitators or vice versa, (2) respect was realized through joint activities including queuing, listening to friends, resolving conflicts between friends, and students who mingle each other.